Swedish free school companies going global: Spatial imaginaries and movable pedagogical ideas. Issue 1 (2nd January 2022) - Rönnberg, Linda; Alexiadou, Nafsika; Benerdal, Malin; Carlbaum, Sara; Holm, Ann-Sofie; Lundahl, Lisbeth
ABSTRACT: Enabled by market-oriented policies implemented in the early 1990s, a nation-wide for-profit education industry has emerged and flourished in Sweden. As a more recent expansion strategy, Swedish school companies have begun exporting their school and early childhood education and care services internationally. In this article, three such companies and a selection of the foreign operations they have set up are studied to analyse how they describe the education services they are establishing in the new national settings. The findings show that the companies have developed and followed different edu-business models, using and transforming particular pedagogical ideas and connecting them to different spatial imaginaries. These include the Swedish/Scandinavian as both places and idealized spaces, infused with borderless global transformative spatial imaginaries on the creation of autonomous learners and futuristic education visions for global futures. Educational profiles and concepts from the Swedish context are both adjusted and marketed to the foreign settings, and entail stories on spaces and mobilities, encompassing pedagogy, teachers and students.